Experimental investigation on the pool boiling characteristics and critical heat flux of Cu-R141b nanorefrigerant under atmospheric pressure. (October 2015) - Diao, Y.H.; Li, C.Z.; Zhao, Y.H.; Liu, Y.; Wang, S.
Highlights: Pool boiling heat transfer characteristic and critical heat flux of Cu-R141b nanorefrigerant is investigated experimentally. Adding surfactant and (or) nanoparticles in pure liquid of R141b could enhance pool boiling heat transfer. The deposition of nanoparticles has a significant effect on the boiling heat transfer. Abstract: The pool boiling heat transfer and critical heat flux (CHF) of the Cu-R141b–SDBS nanorefrigerant and SDBS–R141b solution are experimentally investigated on a flat surface under atmospheric pressure. The nanorefrigerant concentrations are 0.008 vol.%, 0.015 vol.%, and 0.05 vol.%. Pure R141b is also boiled on the nanorefrigerant-deposited surface to isolate the effect of the fluid properties. Experimental results show that the Cu-R141b–SDBS nanorefrigerant can enhance the pool boiling heat transfer. The enhancement ratio of the Cu-R141b–SDBS nanorefrigerant is different from that of the R141b–SDBS solution compared with pure R141b. The CHF of the nanorefrigerant on the bare surface is lower than that of pure R141b on the deposited surface.